CRISPR-Cas Systems and the Paradox of Self-Targeting Spacers - Wimmer, Franziska; Beisel, Chase L. (Frontiers in Microbiology, 2020)
CRISPR-Cas immune systems in bacteria and archaea record prior infections as spacers within each system’s CRISPR arrays. Spacers are normally derived from invasive genetic material and direct the immune system to complementary targets as part of future infections. However, not all spacers appear to be derived from foreign genetic material and instead can originate from the host genome. Their presence poses a paradox, as self-targeting spacers would be expected to induce an autoimmune response and cell death. In this review, we discuss the known frequency of self-targeting spacers in natural CRISPR-Cas systems, how these spacers can be incorporated into CRISPR arrays, and how the host can evade lethal attack. We also discuss how self-targeting spacers can become the basis for alternative functions performed by CRISPR-Cas systems that extend beyond adaptive immunity. Overall, the acquisition of genome-targeting spacers poses a substantial risk but can aid in the host’s evolution and potentially lead to or support new functionalities.